Religion and nothingness - Nishitani, Keiji; King, Winston L. (Winston Lee), 1907-2000; Van Bragt, Jan, 1928-2007 (Berkeley (Calif.) : University of California press, 1982)
Nishitani legt in dit boek westerse filosofieën en religies op de rooster.
Keywords: Religious thought; Religion -- Philosophy; Sunyata